وراثة بعض الصفات الهامة في البازلاء الخضراء (Pisum sativum L.) - أبو ترابي بسام; مخوّل سهيل; العايش فراس (Latakia University Journal -Biological Sciences Series, 2019)
تم تقدير قوة الهجين الوراثية في الجيل الأول، التقهقر الراجع للتربية الذاتية في الجيل الثاني، ومعاملي الارتباط الوراثي والمظهري لصفات عدد الفروع المثمرة/نبات، عدد البذور/قرن، ارتفاع النبات، نسبة التصافي، والغلّة من القرون الخضراء في ستة (6) هجن من البازلاء الخضراء ناتجة عن إدخال أربعة (4) طرز وراثية أبوية في برنامج تهجين نصف متبادل. أظهرت النتائج وجود تباين في أداء الطرز الأبوية المتصالبة ساهم بدوره في إظهار قوة الهجين في الجيل الأول في اتجاهات ومقادير مختلفة وانحدار تلك القوة في الجيل الثاني باتجاه ومقادير مختلفة أيضاً. لوحظت قوة هجين ذات اتجاه مرغوب في الجيل الأول لصفة غلّة النبات من القرون الخضراء لكنها لم تصل مستوى الدلالة، عدا الهجين Oterlo × Mutant-3 (24.71) %، والذي أبدى بذات الوقت القيمة الأعلى للتقهقر في الجيل الثاني (37.16) %؛ ما يشير إلى سيطرة تأثيرات فعل المورثات غير التراكمي لهذه الصفة. تبدو هنالك إمكانية التحسين لصفات عدد البذور/قرن ونسبة التصافي، نسبة التصافي وغلّة النبات من القرون الخضراء عند ممارسة الانتخاب في الأجيال الانعزالية للهجين Oterlo × Dasargelo؛ نظراً لوجود ارتباط موجب عالي الدلالة بينها على كلا المستويين الوراثي والمظهري. Heterosis versus mid-parent in F1, inbreeding depression in F2, genotypic and phenotypic coefficients of correlation for some traits namely; podded branches/plant, seeds/pod, plant height, net ratio of green pods, and green pod yield/plant in six (6) crosses of garden peas produced by 4 x 4 half-diallel crossing scheme had been estimated. Results showed different performance of crossed parental genotypes which involved in heterosis expression of F1 crosses in different directions and magnitudes and also in inbreeding depression of F2. Desirable heterosis in F1 of green pod yield/plant had been observed in all hybrids, but it was not significant, except in Mutant-3 x Oterlo (24.71) % which had also the highest magnitude of inbreeding depression (37.16) %; indicating the predominance of non-additive gene effects. It seems that there is a possibility for improvement of seeds/pod and net ratio of green pods, net ratio of green pods and green pod yield/plant when selection procedures are practiced in segregating generations of Dasargelo x Oterlo; due to positive and highly significant genotypic and phenotypic correlations between them on two both levels. . .